The Moderating Role of Capital Adequacy in the Effect of Liquidity on the Profitability of Islamic Banking - Rury Diwira Registanaranti Yastika; Maria Rio Rita; Imanuel Madea Sakti (Relevance: Journal of Management and Business, 2020)
This study aims to examine the effect of liquidity on profitability with capital adequacy as a moderating variable in Islamic commercial banks in Indonesia. The research sample was 14 Islamic commercial banks during the 2016 - 2018 observation period. The dependent variable is profitability measured using Return On Assets (ROA), the independent variable is liquidity measured using the Financing to Deposit Ratio (FDR), the moderating variable is measured using the Capital Aquendency Ratio (CAR), and several control variables. Non Performing Financing (NPF), Operational Efficiency (BOPO), and Bank Size (SIZE). Hypothesis testing uses multiple linear regression with a random effect model. The results showed that bank liquidity was not proven to increase bank profitability and capital adequacy was not proven to moderate the relationship between the two. The results indicated that the efficiency factor and problematic financing The results indicate that the efficiency factor and non-performing financing are the main factors in influencing bank profitability.